Soil eaten by chacma baboons adsorbs polar plant secondary metabolites representative of those found in their diet - Ta, Chieu Anh Kim; Pebsworth, Paula A.; Liu, Rui; Hillier, Stephen; Gray, Nia; Arnason, John T.; Young, Sera L. (Environmental geochemistry and health, 2018)
Geophagy, the deliberate consumption of earth materials, is common among humans and animals. However, its etiology and function(s) remain poorly understood. The major hypotheses about its adaptive functions are the supplementation of essential elements and the protection against temporary and chronic gastrointestinal (GI) distress. Because much less work has been done on the protection hypothesis, we investigated whether soil eaten by baboons protected their GI tract from plant secondary metabolites (PSMs) and described best laboratory practices for doing so. We tested a soil that baboons eat/preferred, a soil that baboons never eat/non-preferred, and two clay minerals, montmorillonite a 2:1 clay and kaolinite a 1:1 clay. These were processed using a technique that simulated physiological digestion. The phytochemical concentration of 10 compounds representative of three biosynthetic classes of compounds found in the baboon diet was then assessed with and without earth materials using high-performance liquid chromatography with diode-array detection (HPLC–DAD). The preferred soil was white, contained 1% halite, 45% illite/mica, 14% kaolinite, and 0.8% sand; the non-preferred soil was pink, contained 1% goethite and 1% hematite but no halite, 40% illite/mica, 19% kaolinite, and 3% sand. Polar phenolics and alkaloids were generally adsorbed at levels 10× higher than less polar terpenes. In terms of PSM adsorption, the montmorillonite was more effective than the kaolinite, which was more effective than the non-preferred soil, which was more effective than the preferred soil. Our findings suggest that HPLC–DAD is best practice for the assessment of PSM adsorption of earth materials due to its reproducibility and accuracy. Further, soil selection was not based on adsorption of PSMs, but on other criteria such as color, mouth feel, and taste. However, the consumption of earth containing clay minerals could be an effective strategy for protecting the GI tract from PSMs.